-7+12w=-67

Simple and best practice solution for -7+12w=-67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+12w=-67 equation:



-7+12w=-67
We move all terms to the left:
-7+12w-(-67)=0
We add all the numbers together, and all the variables
12w+60=0
We move all terms containing w to the left, all other terms to the right
12w=-60
w=-60/12
w=-5

See similar equations:

| 5x×3=10 | | 4z+36=2(4z+4) | | x*(x+7)=(x+3) | | x+20=20;4 | | (104000-x)/81000=0.91 | | 4-((5/3)x)=-6 | | -.5x-98=-99 | | 5x-1=1/2(108) | | 1/2+2h=17 | | -x2+-16x+28=0 | | -10+(x/3)=-12 | | (1/3)^(2x-3)=5 | | 18=4+n/2 | | -x²-16x+28=0 | | 4(4x-6)=27 | | -7x=4=18 | | Y=1/3x^2-4x+5 | | R(x)=1-2×/4×+3 | | 3c^2+3=10c | | 17v-4=30 | | 56+2x=10x | | 3y=32-y | | ×/3+9/5=x/5+6/5 | | 3x.6-4x.12=0 | | 4(m×m-1)=21 | | F(x)=16^2+32x-9 | | 3x.6=4x.12 | | m/3-5=11 | | 261/8+s=-51/4 | | (5x-7)-5(7x-12+7)=0 | | x+x+38+3x-39=549 | | 15x+8=20x+2 |

Equations solver categories